The Role of Company Profile Videos in Strengthening the Reputation of Girikerto Village Government - Lokananta, Arbi Cristional; Lestari, Rini; Jatisidi, Artyasto; Adisti, Mutiara (Communicare : Journal of Communication Studies, 2025)
The company profile is an increasingly popular and effective public relations (PR) tool in the digital era, aimed at introducing the Kalurahan Girikerto government institution to the public and stakeholders. The formulation of the creation idea involved discussions with the Kalurahan Girikerto Government and Desa Preneur Girikerto, leading to an agreement video-based company profile. The objective was to enhance understanding in building the reputation of the Kalurahan Girikerto Government, Sleman. Company profile video integrates elements of credibility, trustworthiness, reliability, and responsibility through the presentation of accurate data and footage of the daily activities of the Girikerto community. This research has data collection techniques included participatory observation, direct documentation, interviews with the Girikerto Head and the Desa Preneur Girikerto Chairman, and library research. The object of company profile video was determined to be the video company profile of Desa Preneur Girikerto. The design process included data research, idea gathering, concept formulation, media selection, visualization, and production. The company profile video, lasting 00:03:10 (three minutes, ten seconds), was published on the YouTube channel @girikerto, effectively building a positive image and reputation for the Kalurahan Girikerto Government. Overall role of this video company profile is informative and accurate, reflecting the kalurahan's ability to manage digital content. Recommendations for future improvements include enhancing team collaboration, upgrading production equipment and facilities, and optimizing funding to produce higher-quality works.